2021
DOI: 10.4103/jfmpc.jfmpc_1442_20
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine wastage at primary, secondary, and tertiary level of healthcare system—A study from Northern India

Abstract: Background: High vaccine wastage results in escalation of budget of immunization program. Objective: To analyze vaccine wastage at three levels of service delivery under public sector, such as at district level, community health Centre (CHC), and sub center (SC). Study Design: A retrospective cross-sectional record based study in a north Indian state. Materials and Methods: The record from January to June 2016 was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
2
1
0
Order By: Relevance
“…Freeze-dried vaccines had signi cantly higher wastage than liquid vaccines and this concurs which what has been found in several studies [4,13,15,19,23,24]. However, a study in 2012 in India found a negligible difference in wastage of the two vaccine types [3].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Freeze-dried vaccines had signi cantly higher wastage than liquid vaccines and this concurs which what has been found in several studies [4,13,15,19,23,24]. However, a study in 2012 in India found a negligible difference in wastage of the two vaccine types [3].…”
Section: Discussionsupporting
confidence: 82%
“…Larger health facilities had less wastage compared to smaller ones. This concurs with ndings of studies in South Sudan and India in 2021 [4,24] but disagrees with a study in The Gambia in 2018 which found no statistically signi cant difference in wastage [12]. In our study, larger health facilities had more days of static sessions in a month but with larger median session sizes compared to small facilities.…”
Section: Discussionsupporting
confidence: 52%
“…To determine the number of vaccines needed to prevent a malaria adverse outcome (VN), the vaccine wastage (VW) rate needs to be factored in as follows: where DF denotes the number of indicated doses, currently set at four for full-immunization. The propensity of VW increases as (a) the geographical distance from the most advantaged urban center (MA) (G D ), (b) the developmental distance from MA (D D ), and (c) institutional mistrust (I M ) increase [ 12 14 ], that is, subnationally, . Thus, in case only a national average of VW rate is available, then district- or municipality-level VW rates need to be corrected accordingly depending on their G D , D D , and I M .…”
Section: Main Textmentioning
confidence: 99%